Quality and Shelf Life Assessment of Modified Pekasam Ale-ale (Meretrix meretrix) - Nofiani, Risa; Nopianti, Nopianti; Ardiningsih, Puji (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Pekasam ale-ale is spontaneously fermented ale-ale (Meretrix meretrix) flesh with fine salt and incubated for 3-7 days. Modified pekasam ale-ale prepared by adding 155 g of garlic powder into the original pekasam ale-ale showed the best acceptability and had a different quality than the original pekasam ale-ale. The best maturity time and the predicted shelf life for modified pekasam ale-ale fell on days 40 and 60, respectively. Garlic powder has successfully improved the taste and aroma of modified pekasam ale-ale. Abstract Pekasam ale-ale is spontaneously fermented ale-ale (Meretrix meretrix) flesh with fine salt and carbohydrates, such as sugar, rice porridge or angkak (red fermented rice) followed by incubation for 3-7 days. This product has a slightly fishy odour based on the communities’ opinion at Ketapang and its unknown shelf life. The original recipe added granulated sugar and garlic powder might be able to remove the fishy odour. The effects of the addition of both ingredients are still unknown for the quality, consumer acceptability and shelf life. The objective of the study was to evaluate the quality and shelf life of pekasam ale-ale added granulated sugar and garlic powder based on sensory, physicochemical and microbiological profiles. Three recipes for this study were A (1 kg of fresh ale-ale flesh, 400 g of fine salt), B (recipe A, 200 g of granulated sugar, 55 g of garlic powder), and C (recipe A, 200 g of granulated sugar, 125 g of garlic powder) then tested physicochemical, microbiological and sensory properties. The water content, pH, and free fatty acids of A, B, and C differ significantly except for the ash content. All recipes were safe for consumption based on their physicochemical and microbiological properties. The best taste and aroma were awarded to C and B, respectively. The best acceptance score was awarded for C, with days 40 and 60 for the best maturity and shelf life, respectively. In conclusion, garlic powder successfully enhances the taste and aroma and reduces the fishy aroma of pekasam ale-ale.